2014
DOI: 10.1016/j.vetpar.2014.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Heartworm ‘lack of effectiveness’ claims in the Mississippi delta: Computerized analysis of owner compliance – 2004–2011

Abstract: A retrospective medical record review was conducted to identify factors from veterinary clinic medical records that may have contributed to suspected ineffectiveness of a heartworm preventive product. Patient records of 271 dogs, comprising 301 instances of positive heartworm antigen test results while the dogs were receiving heartworm preventive were evaluated. Nineteen veterinary practices in 17 counties and parishes in Arkansas, Louisiana, Mississippi, and Tennessee participated in the study. Records were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
74
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 2 publications
0
74
0
5
Order By: Relevance
“…Alternatively, it can be a reflection of larger market share of products with milbemycin oxime for heartworm prevention over other MLs in the locality. To document any loss of efficacy to MLs, a full history of prevention and annual antigen test would be required [ 35 ]. Therefore, a reduced efficacy of MLs in these Australian cases must be treated as ‘remotely possible’ due to incomplete information [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it can be a reflection of larger market share of products with milbemycin oxime for heartworm prevention over other MLs in the locality. To document any loss of efficacy to MLs, a full history of prevention and annual antigen test would be required [ 35 ]. Therefore, a reduced efficacy of MLs in these Australian cases must be treated as ‘remotely possible’ due to incomplete information [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to available heartworm preventives was previously considered among potential causes of increased reports of failed heartworm prevention in dogs [ 3 ]. Prevention failures have also been attributed to the interplay of factors in the heartworm life-cycle, erratic treatment compliance, as well as diagnostic, prevention and therapeutic variables [ 4 – 7 ]. However, recent research has confirmed that certain heartworm isolates possess reduced susceptibility to macrocyclic lactone preventives [ 5 , 8 – 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…While numerous parasite preventives are currently available for use in dogs, extensive protection against both ecto-and endoparasites usually requires multiple medications often with varying administration routes and directions [29]. Recent research in both the USA and Europe shows owner compliance in the prevention and treatment of internal and external parasites frequently falls short of expert recommendations [30][31][32][33][34]. Within the USA, 73% of dog owners in one survey believed their dog should receive year-round flea and tick preventives but only 13% actually purchased sufficient medication to achieve year-round protection [32], and owner compliance in the correct administration of canine heartworm preventive is documented as well below 100% [30,35].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research in both the USA and Europe shows owner compliance in the prevention and treatment of internal and external parasites frequently falls short of expert recommendations [30][31][32][33][34]. Within the USA, 73% of dog owners in one survey believed their dog should receive year-round flea and tick preventives but only 13% actually purchased sufficient medication to achieve year-round protection [32], and owner compliance in the correct administration of canine heartworm preventive is documented as well below 100% [30,35]. The use of multiple medications may add further hurdles for owners; an analysis of clinic transaction records for 231,565 dogs receiving flea and tick medication showed approximately 66% of owners purchased insufficient protection to provide the veterinarian's recommended yearround protection [31].…”
Section: Discussionmentioning
confidence: 99%